Application of Behavior Change Techniques (BCTs) based on the ADDIE Model in University Tennis - Ping, Huang; Saibon, Jamalsafri; Hamzah, Aswati (Environment-Behaviour Proceedings Journal, 2025)
This study aimed to examine the application and effectiveness of BCTs based on the ADDIE model in college tennis instruction. An experimental approach was employed by integrating the ADDIE model with BCTs.An experimental group received instruction using the ADDIE-based BCTs teaching method, and a control group, which followed traditional teaching methods, was taught for 8 weeks. The results indicated that the experimental group demonstrated superior tennis skills versus the control group. The study concludes that incorporating BCTs based on the ADDIE model into college tennis instruction significantly improves students’ tennis skills and enhances their interest in learning.